Strategic frameworks for understanding employer participation in school‐to‐work programs - Linnehan, Frank; Carolis, Donna De (Strategic Management Journal, 2005)
Abstract The knowledge and skills inherent in human capital are increasingly recognized as the essence of competitive advantage. Extending the emerging literature on capability building, this paper explores the strategic decision of participating in school‐to‐work programs from the transaction cost and resource‐based view of the firm. Using data from a national sample, we find that both strategic perspectives help to explain decisions to participate in school‐to‐work activities. Our findings indicate that school‐to‐work programs and activities may be understood as interorganizational strategies from a transaction cost view and evidence of a firm's motivation to develop human capital to build competitive advantage from a resource‐based view. Implications for school‐to‐work public policy development in the United States and future research are identified. Copyright © 2005 John Wiley & Sons, Ltd.